2012
DOI: 10.1080/01635581.2012.713160
|View full text |Cite
|
Sign up to set email alerts
|

A Multimineral Natural Product from Red Marine Algae Reduces Colon Polyp Formation in C57BL/6 Mice

Abstract: The goal of this study was to determine if a multi-mineral natural product derived from red marine algae, could reduce colon polyp formation in mice on a high fat diet. C57BL/6 mice were maintained for up to 18 months either on a high-fat “Western-style” diet or on a low-fat diet (AIN 76A), with or without the multi-mineral-supplement. To summarize, colon polyps were detected in 22 of 70 mice (31%) on the high-fat diet, but in only 2 of 70 mice (3%) receiving the mineral-supplemented high-fat diet (p<0.0001). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 51 publications
7
41
1
Order By: Relevance
“…An attractive (alternative) hypothesis is that the combination of minerals functions to help control systemic inflammation, a known risk factor for bone mineral loss [44]. In support of this, we observed in the same animal model that mice on the mineral-supplemented diets had fewer colonic polyps than control mice [21,22], and that liver tumor formation was almost completely absent in these animals [23]. Associated with both findings were reduced inflammatory lesions throughout the intestinal tract.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…An attractive (alternative) hypothesis is that the combination of minerals functions to help control systemic inflammation, a known risk factor for bone mineral loss [44]. In support of this, we observed in the same animal model that mice on the mineral-supplemented diets had fewer colonic polyps than control mice [21,22], and that liver tumor formation was almost completely absent in these animals [23]. Associated with both findings were reduced inflammatory lesions throughout the intestinal tract.…”
Section: Discussionmentioning
confidence: 82%
“…, the red marine algae [21,22] and consists entirely of the inorganic minerals (Marigot Ltd, Cork, IE). The product (GRAS 000028) contains approximately 12% calcium and 1% magnesium, but also has detectable levels of 72 other trace minerals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others species of Lithothamnium sp. were shown to be useful as dietary supplements as well and were efficient in chemoprevention of colon polyp formation in animal models (198). These data on the provision of polysaccharides suggest that the use of marine algae as a dietary supplement for anti-inflammatory purposes may provide a novel approach to prebiotics.…”
Section: Prebiotics and Gut Immunitymentioning
confidence: 99%
“…In a recent study, we demonstrated that a multi-mineral-containing natural product derived from the skeletal remains of the red marine algae, Lithothamnion calcareum , suppressed colon polyp formation in mice on a high-fat diet more effectively than did calcium alone [19]. What accounts for the greater effectiveness of the multi-mineral product as compared to calcium alone was not addressed in the in vivo studies.…”
Section: Introductionmentioning
confidence: 99%